การศึกษาความสัมพันธ์ระหว่างกลยุทธ์การแข่งขันกิจกรรมภายในห่วงโซ่คณค่าและผลการดำเนินงานของวิสาหกิจขนาดกลางและขนาดย่อม - ศิริมาศ จินศิริวานิชย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
Clothing & apparel industries in Thailand have been confronted with highly competitive situation due to price cutting from foreign competitors. Then the development of Competitive Strategy and Internal Activities are needed for the manufacturers to maintain their share in this situation. The purposes of this research are to (1) study the relationship between the Competitive Strategy and Value Chain Activities of small and medium size business and (2) study the effects of the Competitive Strategy and Value Chain Activities to the Firm Performances. The sample sizes of this research are small and medium size clothing & apparel industries in Bangkok. The instrument of this research is a questionnaire. 387 questionnaires were sent off and 378 of them reached the companies. 107 of them were completed and sent back which were corresponded to 27.65% response rate. Data analysis was performed by Analysis of variance (ANOVA), Pearson Correlation Coefficient and Multiple Regression Analysis (MRA). The results indicated that Differentiate Strategy and Cost Leadership Strategy gave the higher Customer Performance than the Focus Strategy. The study of relationship betweem Competitive Strategy and Value Chain Acitvities indicated that the Cost Leadership Strategy was related to most Value Chain Activities except those of Marketing & Sales Activities and Service Activities. The Differentiate Strategy was related to all Value Chain Activities. The Focus Strategy was only related to Technology Development. The study of relationship among Competitive Strategy, Value Chain Activities and Firm Performances (Overall Business Performance, Financial Performance, Customer Service Performance, Internal Business Performance and Learning and Growth Performance) showed that Operational Activities, Service Activities and Technology Development could predict Overall Business Performance that accounted for 54.3 percents of variance (R[superscript 2]=54.3). The Marketing & Sale Activities and Human Resource Management could predict Financial Performance that accounted for 52 percents of variance (R [superscript 2]=52). The Service Activities and Infrastructure could predict Customer Service Performance that accounted for 38.3 percents of variance (R [superscript 2]=38.3). The Inbound Activities, Service Activities and Firm Infrastructure could predict Internal Business performances that accounted for 42.5 percents of variance (R [superscript 2] 42.5). Finally the Marketing & Sales Activities and Technology Development could predict Learning and Growth Performance that accounted for 42.9 percents of variance (R [superscript 2]=42.9).